Association between Active Transportation and Public Transport with an Objectively Measured Meeting of Moderate-to-Vigorous Physical Activity and Daily Steps Guidelines in Adults by Sex from Eight Latin American Countries - Herreros Irarrázabal, Diego (2021)
This study aimed to examine the associations between active transportation and public transport and the objectively measured meeting of moderate-to-vigorous physical activity (MVPA) and steps per day guidelines in adults by sex from eight Latin American countries. As part of the Latin American Study of Nutrition and Health (ELANS), data were collected from 2524 participants aged 18–65 years. MVPA and steps per day were evaluated using Actigraph GT3X accelerometers. The mode of transportation, its frequency and duration were collected using a self-reported questionnaire. The average time dedicated to active transportation was 12.8 min/day in men (IQR2.8–30.0) and 12.9 min/day in women (IQR: 4.3–25.7). A logistic regression analysis was conducted, showing that active transportation (≥10 min) was associated with higher odds of meeting MVPA guidelines (men: OR: 2.01; 95%CI: 1.58–2.54; women: OR: 1.57; 95%CI: 1.25–1.96). These results show a greater association when considering active transportation plus public transport (men: OR: 2.98; 95%CI: 2.31–3.91; women: OR: 1.82; 95%CI: 1.45–2.29). Active transportation plus public transport was positively associated with meeting steps per day guidelines only in men (OR: 1.55; 95%CI: 1.15– 2.10). This study supports the suggestion that active transportation plus public transport is significantly associated with meeting the MVPA and daily steps recommendations.